Wyłącz wspólny czynnik przed nawias:
a) 4x-8y-4z=
6a-9b+12y=
12a²+8m-20=
b)5a²-15b+20c=
30x+18y-6=
36a+12b-6=
c)63m+54n-9=
3a²/5+6b/5-9/5=
3,5a+0,7b-14=
Wyłącz wspólny czynnik przed nawias:
a)-8x+6y-2=
b)6a-12b+18c=
c)21x²+14y³-7=
d)-1,6a-0,8b-4,8c=
e)⅘x+⅗y+1/5=
f)3¾a+6¼b-1¼=

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-30T14:21:50+02:00
A) 4x-8y-4z=4(x-2y-z)
6a-9b+12y=3(2a-3b+4y)
12a²+8m-20=4(3a²+2m-5)
b)5a²-15b+20c=5(a²-3b+4c)
30x+18y-6=6(5x+3y-1)
36a+12b-6=6(6a+2b-1)
c)63m+54n-9=9(7m+6n-1)
3a²/5+6b/5-9/5=3/5(a²+2b-3)
3,5a+0,7b-14=0,7(5a+b-20)
Wyłącz wspólny czynnik przed nawias:
a)-8x+6y-2=2(-4x+3y-1)
b)6a-12b+18c=6(a-2b+3c)
c)21x²+14y³-7=7(3x²+2y³-1)
d)-1,6a-0,8b-4,8c=-0,8(+2a+b+6c)
e)⅘x+⅗y+1/5=1/5(4x+2y+1)
f)3¾a+6¼b-1¼= 5/4(3+5-1)
2010-03-30T14:25:23+02:00
4x-8y-4z=4(x-2y-z)
6a-9b+12y=3(2a-3+4y)
12a²+8m-20=4(3a²+2m+5)
b)5a²-15b+20c=5(a²-3b+4c)
30x+18y-6=6(5x+3y-1)
36a+12b-6=6(6a+2b-1)
c)63m+54n-9=9(7m+6n-1)
3,5a+0,7b-14=0,7(5a+1b+20)

a)-8x+6y-2=2(-4x+3y-1)
b)6a-12b+18c=6(a-2b+3c)
c)21x²+14y³-7=7(3x²+2y³-1)
d)-1,6a-0,8b-4,8c=0,8(-2a-1b-6c)